2023
DOI: 10.3390/molecules28083469
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Pharmacological Activities of Pachypodol: A Bioactive Compound of an Aromatic Medicinal Plant Pogostemon Cablin Benth

Abstract: As is well known, plant products have been increasingly utilized in the pharmaceutical industry in recent years. By combining conventional techniques and modern methodology, the future of phytomedicines appears promising. Pogostemon Cablin (patchouli) is an important herb used frequently in the fragrance industries and has various therapeutic benefits. Traditional medicine has long used the essential oil of patchouli (P. cablin) as a flavoring agent recognized by the FDA. This is a gold mine for battling patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Currently, PEO stands as a pivotal ingredient in cosmetic products, valued for its herbaceous notes and fixative properties. Pharmacological studies have revealed that PEO has diverse bioactive components, which demonstrate anti-allergic and anti-acne properties, and antibacterial effects on the skin, as well as anti-oxidative and anti-inflammatory benefits [23][24][25]. A previous study by Lin et al [20] reported that the topical application of patchouli oil prevents the cutaneous photoaging induced by UV radiation in mice by enhancing the skin's antioxidant defense mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, PEO stands as a pivotal ingredient in cosmetic products, valued for its herbaceous notes and fixative properties. Pharmacological studies have revealed that PEO has diverse bioactive components, which demonstrate anti-allergic and anti-acne properties, and antibacterial effects on the skin, as well as anti-oxidative and anti-inflammatory benefits [23][24][25]. A previous study by Lin et al [20] reported that the topical application of patchouli oil prevents the cutaneous photoaging induced by UV radiation in mice by enhancing the skin's antioxidant defense mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also purified PO using a rotary evaporator to obtain light and high fractions of PO [21]. The light and high fractions were fractionated at 60°C-65°C and 115°C-160°C, respectively [21].…”
Section: Discussionmentioning
confidence: 99%
“…This plant is an herbal plant that people believe to be a therapeutic plant. P. cablin contained various biologically active components, including terpenoids, aldehydes, alkaloids, lignin, organic acids, alcohols, phytosterols, flavonoids, and glycosides [21]. This plant was also known as an aphrodisiac because it raises the secretion of the sex hormones estrogen and testosterone, thus supporting the disappearance of sexual fears and sluggish libido [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we took Pogostemon cablin for green synthesis and compared it with chemically synthesized TiO 2 NPs. The leaf extract of Pogostemon cablin is the richest source of secondary metabolites like alkaloids, phenolics, flavonoids and terpenoids [31][32][33]. A previous study reported that plants containing secondary metabolites can reduce metal salts into NPs, stabilize them, and serve as a capping agent [34].…”
Section: Introductionmentioning
confidence: 99%